Comparative Study of Five-Level and Seven-Level Inverter Controlled by Space Vector Pulse Width Modulation - Abdelmalik Bendaikha; Salah Saad (Institute of Advanced Engineering and Science, 2017)
This paper presents a MATLAB/SIMULINK model of two multi-level inverter topologies. Algorithms based on space vector modulation (SVM) technique are developed in order to conduct a comparative study on diode clamped five and seven level inverters. The scheme used to develop these control algorithms are based on symmetrical sequence because of the symmetry of the switching wave. Both topologies are simulated and analyzed using a squirrel cage induction motor. The results have showed that the best motor dynamic response with less harmonic distortion and torque fluctuations is obtained when seven-level inverter is employed.